Excellent Absorption of LaCoxO3 Over Full Solar Spectrum and Direct Photothermal Energy Storage of Ca(OH)2–LaCoxO3 (Journal of Solar Energy Research Updates, 2023)
Abstract: Photothermal conversion is a vital way for solar energy applications. The strong absorption of near Infrared light is essential for excellent photothermal performance. In this study, we demonstrated that nano LaCoxO3 is able to harvest light intensely across the full solar spectrum with high photothermal temperature. A core-shell-like structure of LaCoxO3-coated Ca(OH)2 particles was fabricated and shows excellent photothermal conversion, high kinetics of dehydration and remarkable cycle stability of heat storage and release. The photothermal dehydration-conversion of Ca(OH)2 increases 8.4-fold. Results demonstrate the multifunctionality of LaCoxO3, intensifying light harvesting, high photothermal conversion, good stability, considerable strength, and porous framework favouring the performance of photothermal storage and release cycles. LaCoxO3–Ca(OH)2 composite can simultaneously harvest light and store thermal energy.